2016
DOI: 10.1371/journal.pone.0152518
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Effects of (–)-Epigallocatechin Gallate (EGCG) on Pristane-Induced Arthritis (PIA) in Female Dark Agouti Rats

Abstract: Rheumatoid arthritis (RA)—a widespread chronic inflammatory disease in industrialized countries—is characterized by a persistent and progressive joint destruction. The chronic pro-inflammatory state results from a mutual activation of the innate and the adaptive immune system, while the exact pathogenesis mechanism is still under discussion. New data suggest a role of the innate immune system and especially polymorphonuclear granulocytes (PMNs, neutrophils) not only during onset and the destructive phase of RA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 70 publications
1
32
0
Order By: Relevance
“…Morinobu et al focused their study on the role of nuclear factor of activated T cells c1 (NF-ATc1) in EGCG’s effect on osteoclasts [35]. On the other hand, a study by Leichsenring, et al lacked a detailed discussion on the mechanism of EGCG [34]. A study of Oka, et al on both EGCG and TFDG also gave an incomplete description of the mechanism of the compounds’ anti-RA effects [36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Morinobu et al focused their study on the role of nuclear factor of activated T cells c1 (NF-ATc1) in EGCG’s effect on osteoclasts [35]. On the other hand, a study by Leichsenring, et al lacked a detailed discussion on the mechanism of EGCG [34]. A study of Oka, et al on both EGCG and TFDG also gave an incomplete description of the mechanism of the compounds’ anti-RA effects [36].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, IL-6, TNFα, and interferon (IFN)-γ were suppressed, but anti-CII specific IgG1 antibodies were activated when CIA rats were treated for 3 weeks with a dose of 10 mg per kg of the rats’ weight [33]. EGCG at doses of 10 mg/kg for 5 days also showed anti-RA effects on pristane-induced arthritic (PIA) rats via inhibition of myeloperoxidase (MPO) [34]. When both human osteoclasts of peripheral blood monocytes and mice were treated for 15 days with a dose of 20 and 50 μM, CTR, carbonic anhydrase II, cathepsin K, α-v integrin, β-3 integrin, and NF-ATc1 were downregulated [35].…”
Section: Polyphenols and Rheumatoid Arthritismentioning
confidence: 99%
“…Two groups of Wistar albino rats weighing around 200-250 g were used to study the pharmacokinetics after a single oral administration of free EGCG and Alb-NP-EGCG at a dose of 10 mg kg −1 (Leichsenring et al 2016;Stringer et al 2017). Rats were sacrificed at a time interval of 1, 2, 3, 4, 6, 8, and 24 h after oral drug administration and the blood and tissue samples (liver, kidney, spleen, and brain) were collected.…”
Section: Dosing Of Rat and Sample Collectionmentioning
confidence: 99%
“…Green tea consumption has been associated with multiple health benefits, particularly its active derivative epigallocatechin-3-gallate (EGCG) has shown to modulate many pharmacological properties in cancer (Lambert and Yang 2003;Thangapazham et al 2007;Rahmani et al 2015), inflammatory (Tominari et al 2015;Leichsenring et al 2016) and cardiovascular diseases (Eng et al 2018). Further, EGCG has shown the potential to inhibit reactive oxygen species and apoptosis, chelate metals, and modulate multiple signaling pathways (Hechler et al 2006;Karatas et al 2009;Schroeder et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…For example, a randomized, double-blind, placebo-controlled trial showed that green tea containing O -methylated catechins reduces symptoms of Japanese cedar pollinosis [ 100 ]. In an animal model of arthritis, the therapeutic effect of EGCG was reported to be comparable to that of methotrexate, a well-known anti-rheumatoid arthritis drug [ 101 ]. CMDA provided information on the interaction of catechins with proteins related to immunological diseases and two studies [ 102 , 103 ] have been discussed earlier [ 5 ].…”
Section: Cmda Of Catechin-protein Interactionmentioning
confidence: 99%